Autonomic reactivity to cognitive and emotional stress of low, medium, and high hypnotizable healthy subjects: testing predictions from the High Risk Model of Threat Perception. - Jørgensen MM; Zachariae R (International Journal of Clinical & Experimental Hypnosis, 2002)
This study tested hypotheses derived from Wickramasekera's High Risk Model of Threat Perception (HRMTP) by comparing autonomic and affective responses to a cognitive and an emotional stress task in high, medium, and low hypnotizables. Electrodermal activity (EDA) was used as a measure of sympathetic activity, and the high frequency (HF) spectral component of heart rate variability as a measure of parasympathetic activity. High hypnotizables exhibited greater EDA at baseline and slower EDA recovery following both tasks than did medium and lows. Medium hypnotizables responded with greater decreases in normalized HF power than did highs and lows during the emotional stress task. The results suggest diminished EDA variability in high hypnotizables and the potential for HF power as an indicator of autonomic dysregulation in low and high hypnotizables, compared to mediums. The results are discussed in relation to predictions based on the HRMTP.